The Relationship between the Level of Adherence to Antenatal Care and the Incidence of Chronic Energy Deficiency among Pregnant Women in Areas with a High Prevalence of Intellectual Disabilities - Aniek Luftyannisa; Arief Prijatna (Jurnal Sehat Indonesia (JUSINDO), 2026)
Chronic energy deficiency among pregnant women remains an important maternal nutrition problem because it may increase the risk of adverse pregnancy outcomes and reflects inadequate nutritional status during pregnancy. Antenatal care adherence is expected to support early detection and prevention of nutritional disorders through routine maternal assessment, nutritional counseling, and anthropometric monitoring. This study aimed to analyze the relationship between antenatal care adherence and the incidence of chronic energy deficiency among pregnant women in Karangpatihan Village, Balong District, Ponorogo Regency, an area known for a high prevalence of intellectual disability. This study used an analytic observational design with a cross-sectional approach. The study population consisted of pregnant women who met the inclusion criteria and had complete data on antenatal care visits and mid-upper arm circumference measurement. Antenatal care adherence was categorized as adherent when respondents completed at least six visits and non-adherent when fewer than six visits were recorded. Chronic energy deficiency was defined as mid-upper arm circumference below 23.5 cm. Data were analyzed using the Chi-Square test. Among 70 respondents, 42 respondents (60%) were non-adherent to antenatal care and 39 respondents (55.7%) experienced chronic energy deficiency. Bivariate analysis showed a significant relationship between antenatal care adherence and chronic energy deficiency (p = 0.001; OR = 0.189; 95% CI: 0.067–0.535). These findings indicate that antenatal care adherence may have a protective role against chronic energy deficiency among pregnant women.